Curriculum-based library instruction : from cultivating faculty relationships to assessment - Blevins, Amy, 1981-; Inman, Megan, 1983- (Medical Library Association books., 2014)
Curriculum-Based Library Instruction: From Cultivating Faculty Relationships to Assessment highlights the movement beyond one-shot instruction sessions, specifically focusing on situations where academic librarians have developed curriculum based sessions and/or become involved in curriculum committees.